2018
DOI: 10.1007/s00394-018-1616-2
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation prevents endothelial dysfunction and attenuates structural changes in aortas from hypothalamic obese rats

Abstract: Our study presents the first evidence that Tau prevents disruptions in vascular reactivity and in extracellular matrix composition in thoracic aortas of MSG-obese rats. The vascular protective actions of Tau may be linked to reduced lipid peroxidation and a reduction in cardiovascular risk factors, such as abdominal fat and hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Aortic rings from MSG group showed reduced endothelium-dependent vasodilation to ACh compared to the control group, indicating the presence of endothelium dysfunction, as we have previously shown [ 34 , 35 ]. Maximal relaxation in response to ACh was 76.91 ± 2.94% and 31.60 ± 1.85% in control and MSG aorta, respectively ( p < 0.05).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Aortic rings from MSG group showed reduced endothelium-dependent vasodilation to ACh compared to the control group, indicating the presence of endothelium dysfunction, as we have previously shown [ 34 , 35 ]. Maximal relaxation in response to ACh was 76.91 ± 2.94% and 31.60 ± 1.85% in control and MSG aorta, respectively ( p < 0.05).…”
Section: Resultssupporting
confidence: 67%
“…After euthanasia, perigonadal and retroperitoneal fat pads were collected and weighed. Obesity was confirmed by the increase in fat stores, despite the reduction in body weight, as described in our previous publications where MSG-induced obesity was used [ 34 , 35 ]. All MSG rats used in this study presented these characteristics.…”
Section: Methodsmentioning
confidence: 96%
“…Borck et al [31] noticed that 5% taurine solution given to obese mice with drinking water for 12 months decreased TAG and improved glucose tolerance and insulin sensitivity. In another study conducted by this team, 2.5% TAU solution given to hypothalamic obese rats for a shorter period (130 days) did not affect the fasting glucose level, but decreased the insulin and TAG concentration [32]. These results support the hypothesis that taurine supplementation may prevent diabetes in obese subjects.…”
Section: Discussionsupporting
confidence: 57%
“…The rapid growth and distant metastasis of tumors depended on a large number of blood vessels to supply the required oxygen and nutrients, and the expression profiles showed that endothelial cells also transported and metabolized large amounts of taurine. Previous studies have revealed that taurine can exert vascular protective effects by reducing lipid peroxidation [64] ; however, the role of taurine in tumor neovascularization requires further exploration.…”
Section: Discussionmentioning
confidence: 99%